nxiety Levels of Couples of Childbearing Age Regarding Interest in Using Contraceptive Implants in the Working Area of the Mopah Baru Community Health Center, Merauke, South Papua 2023 - Husnul H Tuhuteru; Tri Hastuti; Hans Angelius Suharto; Erma Retnaningtyas (Journal of Health Science Community, 2024)
The implant contraceptive method is one of the long-term contraception methods that is less popular with the public, especially couples of childbearing age. This study aims to determine The relationship between anxiety levels of couples of childbearing age and interest in using birth control implants in the working area of ​​the Mopah Baru Community Health Center, Merauke, South Papua 2023. This research uses descriptive research. The research design uses survey research. With technique purposive sampling A sample of 87 respondents was obtained, the independent variable (anxiety level) and the dependent variable (interest in using birth control implants) used a questionnaire. Statistical tests are used Chi-Square to find out the relationship between the two variables. Research results from 87 respondents were obtained sThe majority had a mild level of anxiety about using contraceptive implants, namely 47 respondents (54%), and sThe majority of respondents have a low interest in the use of KB implants, namely 74 respondents (85.1%). Analysis uses statistical tests Chi-Square found there the relationship between the level of anxiety of fertile age couples and their interest in the use of contraceptive implants that is p value = 0,016 < 0,05. It is necessary to seek various sources of information from various parties (for example through print media, electronic media, through friends, family and competent health workers) before making a decision, especially information about the side effects and limitations of birth control implants, so that respondents are not anxious and can have an interest in the use of birth control implants.